Profiling of RNA N6-Methyladenosine Methylation Reveals the Critical Role of m6A in Chicken Adipose Deposition - Cheng, Bohan; Leng, Li; Li, Ziwei; Wang, Weijia; Jing, Yang; Li, Yudong; Wang, Ning; Li, Hui; Wang, Shouzhi (Frontiers in Cell and Developmental Biology, 2021)
One of the main objectives of broiler breeding is to prevent excessive abdominal adipose deposition. The role of RNA modification in adipose deposition is not clear. This study was aimed to map m6A modification landscape in chicken adipose tissue. MeRIP-seq was performed to compare the differences in m6A methylation pattern between fat and lean broilers. We found that start codons, stop codons, coding regions, and 3′-untranslated regions were generally enriched for m6A peaks. The high m6A methylated genes (fat birds vs. lean birds) were primarily associated with fatty acid biosynthesis and fatty acid metabolism, while the low m6A methylated genes were mainly involved in processes associated with development. Furthermore, we found that the mRNA levels of many genes may be regulated by m6A modification. This is the first comprehensive characterization of m6A patterns in the chicken adipose transcriptome, and provides a basis for studying the role of m6A modification in fat deposition.